Pembatasan Kebebasan Berkontrak pada Perjanjian tidak Bernama dalam Bentuk Akta Notaris - Devi, Fatma; Azheri, Busyra; Yulfasni, Yulfasni (Universitas Ekasakti, 2023)
This paper aims to determine control as freedom of contract in the system and the company's position in the engagement. The method uses normative juridical with primary and secondary data. Agreements or commonly called contracts in Indonesia, there are two types of classification when distinguished by name, namely name or name agreements and nameless agreements or named names. The two groups have their own definitions, requirements, elements and legal basis. Unnamed agreements generally grow and develop in society and in practice there are still those that do not have clear arrangements because anonymous agreements are legally recognized by law for their existence as a consequence of the form of agreements in Indonesia which are written and unwritten. The terms of the validity of the agreement, both subjective terms and objective terms, are generally applicable for nameless agreements and nameless agreements. Article 1338 of the Civil Code is the main pillar of the principle of freedom of contract, although in practice it is not free in the true sense, but free with limitations. The agreement made by the parties can be in the form of a private deed or an authentic deed, namely in the form of a Notary Deed and a private deed. The existence of an obligation to the public that certain contracts must follow the rules that have been determined by both the official who made it is one of the efforts for the state to have uniformity and ease of supervision or implementation. The role of a notary in making an anonymous deed agreement in a notarized deed is very useful and has perfect evidentiary power, both formal and material. A notary is a public official who frames the agreement of both parties or more, to make a deed agreement in the form of a notarial deed. The notary must pay attention to the clauses that are prohibited by law and must comply with the things that have been regulated by law.